1984
DOI: 10.2214/ajr.143.4.869
|View full text |Cite
|
Sign up to set email alerts
|

Iopamidol and metrizamide for myelography: prospective double-blind clinical trial

Abstract: In a comparative randomizeddouble-blind study, 73 patients underwent myelography using iopamidol (36 patients) or metrizamide (37 patients) as contrast medium. The overall diagnostic adequacy of iopamidol myelography was found to be comparable to that of metrizamide myelography. The incidence of examinations graded as superior (64%) or adequate (36%) with iopamidol was equivalent to that with metrizamide (57% superior, 43% adequate). Adverse reactions after iopamidol myelography were fewer, less severe, and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Therefore, they suggested that individual sensitivity to iopamidol was an important factor. In other studies, there have been no seizures noted in series of 100 1121,80 15},65 [21,30 131,36 [4], and 21 patients 171.…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, they suggested that individual sensitivity to iopamidol was an important factor. In other studies, there have been no seizures noted in series of 100 1121,80 15},65 [21,30 131,36 [4], and 21 patients 171.…”
Section: Discussionmentioning
confidence: 83%
“…Although animal studies have shown iopamidol to be more epileptogenic than metrizamide 45 and the excitative neurotoxic potential of iodixanol, 46 clinical trials of these newer nonionic agents have shown them to be safe and effective, with fewer adverse effects than metrizamide. 8,16,22,47 The risk of seizure with the currently used contrast media is reported to be in the range of 0.093%-0.847%. 19,48 Review of the literature revealed only case reports of seizure activity after myelography with iopamidol 13,21 and iohexol (On-line Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…In the 1970s, metrizamide, the first non-ionic water-soluble contrast agent, came into use [14]. In the next decade, Iohexol and Iopamidol were developed [15,16]. Although the contrast agents used today are not completely risk-free, they have much lighter side effects than the previous ones [17,18].…”
Section: Brief Historymentioning
confidence: 99%